Outstanding! : 47 ways to make your organization exceptional - Miller, John G., 1958- (New York : G.P. Putnam's Sons, 2010)
The bestselling author of'QBQ!' shows how anyone can use the unlimited potential of accountability to create an outstanding organization. Miller's newest book offers practical ideas for creating a distinguished group with which customers will want to work.
Keywords: Organizational effectiveness; Organizational change; Customer services